With a little help from my peers: professional development of higher education teachers to teach critical thinking (Revista Lusófona de Educação, 2019)
Critical Thinking (CT) has become a fundamental competence of the 21st century. However, university teachers still face several difficulties in promoting it through their teaching practice, mainly due to the lack of pedagogical training aimed at this purpose. In the scope of the CRITHINKEDU Erasmus+ project, a 5-day European training course for university teachers was held in Rome (Italy) aiming to engage participants with CT teaching practices and to prepare them with the required tools suitable for its development. Some teachers from the University of Trás-os-Montes e Alto Douro (UTAD) attended the course as trainees, and later, along with other colleagues, assumed the role of trainers during its replication in Vila Real (Portugal). Through the analysis of a focus group of eight teachers from UTAD, the current exploratory case study aims to understand teachers’ conceptions on CT and characterize how those are integrated in the teaching practices. It also tries to evaluate the impact that both training courses (as trainees and/or trainers) had on their professional development. Preliminary reflections on the implementation of CT teaching practices and the design of teacher's training courses in this field are discussed.Keywords: critical thinking; teaching practice; teacher training; professional development; higher education